Brainy Africans to fortress Europe: For money or colonial vestiges? - Amelie F. Constant; Bienvenue N. Tien (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Economic reasons along with cultural affinities and the existence of networks have been the main determinants explaining migration flows between home and host countries. This paper reconsiders these approaches combined with the gravity model and empirically tests the hypothesis that ex-colonial links can still play an important role in the emigration decision. We employ a general linear mixed model, and apply it to the case of skilled, educated and talented Africans, who migrate to Fortress Europe over the period of 1990 to 2001. While we find some differences in the exodus of skilled Africans by sub-regions, the magnitude of the colonial vestige in Africa is a significant determinant of emigration flows. Overall, Portugal is preferred to the UK which is preferred more than Belgium, Germany and Italy. Brainy Africans are, however, indifferent between the UK, France and Spain as a destination country. Established immigrant networks and higher standards of living with job opportunities in the host country are also very important drivers of the emigration of brainy Africans to the European ex-colonial powers.
Keywords: F22; O15; J61; 330; Skilled migration; Africa; colonization; networks; economic reasons; Brain Drain; Afrikaner; Einwanderung; Kolonialismus; Afrika; EU-Staaten